2018
DOI: 10.1158/0008-5472.can-18-0822
|View full text |Cite
|
Sign up to set email alerts
|

CSTF2-Induced Shortening of the RAC1 3′UTR Promotes the Pathogenesis of Urothelial Carcinoma of the Bladder

Abstract: Shortening of the 3' untranslated regions (3'UTR) of mRNA is an important mechanism for oncogene activation. However, 3'UTR alteration events, their pathologic functions, and underlying mechanisms in human urothelial carcinoma of the bladder (UCB) are not clear. Here, we combine RNA sequencing, bioinformatics, and clinical studies in two independent cohorts of patients with UCB to identify a novel shorter 3'UTR isoform that is frequently expressed in UCB and is critical in the tumorigenesis and acquisition of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 39 publications
0
69
0
Order By: Relevance
“…We processed the tumor and normal aligned files to generate coverage files that were used as an input for the DaPars (Dynamic Analysis of Alternative Polyadenylation from RNA-Seq) algorithm 41 . DaPars is a regression-based algorithm that performs de-novo identification of APA events between two conditions using standard RNA-seq data 32,33,41 . DaPars generates a mean PDUI score (Percentage Distal Usage Index) for each gene, quantifying the extent of usage of the distal PAS across each group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We processed the tumor and normal aligned files to generate coverage files that were used as an input for the DaPars (Dynamic Analysis of Alternative Polyadenylation from RNA-Seq) algorithm 41 . DaPars is a regression-based algorithm that performs de-novo identification of APA events between two conditions using standard RNA-seq data 32,33,41 . DaPars generates a mean PDUI score (Percentage Distal Usage Index) for each gene, quantifying the extent of usage of the distal PAS across each group.…”
Section: Resultsmentioning
confidence: 99%
“…4). CSTF2 has previously been implicated as a promoter of lung and bladder cancer, through the regulation of ERBB2 and RAC1 3’-UTRs, respectively 33,34 . We find frequent 3’-UTR alterations in several notable PDA-relevant genes whose mechanisms of regulation were previously unknown, including PAF1 , ALDOA and FLNA .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The shortening of mRNA 3′‐UTRs results in the activation of oncogenes and the repression of tumor suppressors 9,10 . It has been reported that 3′‐UTR shortening of certain genes could enhance tumor cell proliferation, migration, and invasion 11‐13 . In addition, shorter 3′‐UTRs of target genes were associated with poor prognosis of certain tumors, such as breast, lung, colorectal, and bladder cancers 13‐15 .…”
Section: Introductionmentioning
confidence: 99%